A study of histological responses from Ti-6Al-7Nb alloy dental implants with and without plasma-sprayed hydroxyapatite coating in dogs - Lavos-Valereto, I. C.; Konig, B.; Rossa, C.; Marcantonio, E.; Zavaglia, A. C. (Springer, 2001)
Titanium alloys are hoped to be used much more for applications as implant materials in the medical and dental fields because of their basic properties, such as biocompatibility, corrosion resistance and specific strength compared with other metallic implant materials. Thus, the Ti-6Al-7Nb alloy that has recently been developed for biomedical use, that is, primarily developed for orthopaedic use, is to be studied in this paper, for application in dental implants. The biocompatibility test in vivo was carried out in dogs and the osseointegration was verified through histological analysis of the samples of the Ti-6Al-7Nb alloy with and without hydroxyapatite coating that were inserted in the alveoli. Within the controlled conditions the samples did not show any toxic effects on the cells. (C) 2001 Kluwer Academic Publishers.